The adolescent health and youth development program a strategic plan - Lilam, Gilda L. (Davao City U.P. in Mindanao, 2001)
The population programs for General Santos City are anchored in the Commission on Population which is the lead agency and coordinator of the Philippine Population Management Program where the Adolescent Health and Youth Development Program is a major program component.

These programs, which receive technical and resource assistance from the United Nations Population Fund, seeks to prepare Filipino youths for responsible adulthood by addressing their needs related to adolescent sexuality within the context of healthy and wholesome adolescent development.

The forerunners of the AHYDP were the Population Education Programs of the Department of Education Culture and Sports and the Philippine Awareness Program of the Department of Social Welfare and Development. The AHYDP is a component of UNFPA's Fourth Country Program known as "Support to the Adolescent Fertility and Youth Development Program, (1994, 1998).

At the local level, General Santos takes the lead in the overall coordination of program implementation. It will coordinate with government agencies and locally-based non-government organizations within the city and with people's organizations that are located within the city and neighboring areas.

In addressing the needs of the youths, the program will promote and encourage positive life choices among the youths will provide

relevant and adequate services. It will support adolescents to postpone sexual activity, manage the risks to health and well-being from adolescent sexual activities, promote later marriages, and adopt wholesome activities to general relations and sexual matters.

It will further seek to help in the proper information of values of young Filipinos so that biological urges are managed with prudence and wisdom, as well as with a consciousness of wider life concerns. The program also recognizes that parents and professionals working with the young and influentials or decision makers play a very important role and reach out to them as well.

Information, Education, and Communication (IEC) is one of the program's main tools for the proper formation of young Filipino hearts and minds. This involves undertaking communications and advocacy activities that seek to increase the responsiveness of the youth to population and gender concerns through their own private behavior, their participation in community governing structures and their involvement in other social concerns, such as those related to environmental protection.

The target audience of this program will be the urban and rural Filipinos, 15-24 years old. The parents will be the secondary target audience while the tertiary audience will consist of the professionals working with the youth, such as teachers and counselors and decision makers , such as the local government officials.
Strategic plan (M.M.)--U.P. in Mindanao, 2001.
Includes bibliographical references and index.
Keywords: Strategic planning; Teenagers (General Santos City, Philippines).; Teenagers -- Health and hygiene (General Santos City, Philippines).; Youth (General Santos City, Philippines; Youth -- Health and hygiene (Genaeral Santos City, Philippines).; Strategic plans; General Santos City (Philippines).